التواصل الحضاري بين المغرب الأقصى وبلاد السودان الغربي خلال العصر الحديث ( القرنين 9 ه-11ه/ 15 م – 17 م ) - خالدي يسرى; بن يزة إلهام (My University, 2022)
Abstract Scientific cross-pollination constituted one of the most prominent areas of cultural interaction between the cities of Western Sudan and the Maghreb. These ties between the two countries developed with the migration of an elite group from Morocco to the cities of Western Sudan. They were able to influence scientific and cultural life as a result of their scholarly activity, particularly among scholars, jurists, preachers, and merchants. They developed the educational process, authored books, built mosques, and constructed schools. They were instrumental in spreading Islam and the Arabic language, transforming some cultural centers into beacons of knowledge. There is no doubt that the scholars of Western Sudan played a significant role in the flourishing of intellectual life in Morocco. Thus, manifestations of scientific influence and influence, as well as exchanges, are numerous between scholars from the Sudanese cities and their counterparts in Morocco. ------------------------------------- الملخص شكل التلاقح العلمي أحد أبرز ميادين التفاعل الحضاري بين مدن السودان الغربي وبلاد المغرب الأقصى،وقد تطورت هذه الروابط بين القطرين بانتقال نخبة من المغرب الأقصى إلى حواضر السودان الغربي واستطاعت التأثير على الحياة العلمية والثقافية نتيجة لنشاطهم العلمي ، خاصة فئة العلماء و الفقهاء والدعاة والتجار، حيث طوروا العملية التعليمية وألفوا الكتب و شيدوا المساجد وبنوا المدارس ، فكان لهم الفضل في نشر الإسلام واللغة العربية، وحولوا بعض المراكز الثقافية إلى منارات علمية، ومما لا شك فيه أن علماء السودان الغربي فضل كبير في ازدهار الحياة الفكرية في المغرب الأقصى ، إذا فان مظاهر التأثير و التأثر العلمي والأخذ والعطاء متعددة بين علماء الحواضر السودانية و نظيرتها بالمغرب الأقصى. ------------------------------------------ Résumé Le brassage scientifique a été l'un des principaux domaines d'interaction culturelle entre les villes du Soudan occidental et les pays du Maghreb extrême. Ces liens entre les deux pays se sont développés avec la migration d'une élite du Maghreb extrême vers les villes du Soudan occidental. Grâce à leur activité scientifique, ils ont pu influencer la vie scientifique et culturelle, en particulier celle des érudits, des juristes, des prédicateurs et des marchands, qui ont développé le système éducatif, écrit des livres, construit des mosquées et des écoles. On leur attribue la diffusion de l'islam et de la langue arabe, et la transformation de certains centres culturels en pôles scientifiques. Il ne fait aucun doute que les érudits du Soudan occidental ont joué un rôle majeur dans l'épanouissement de la vie intellectuelle au Maghreb extrême. Par conséquent, les manifestations d'influence et d'impact scientifiques, ainsi que les échanges mutuels, sont multiples entre les érudits des villes soudanaises et leurs homologues du Maghreb extrême.
Keywords: التفاعل الحضاري – المغرب الأقصى – السودان الغربي – المراكز الثقافية